Cross-cultural impact of (in)genuine, smiling celebrities in online advertising - Peter Broeder; Daphne Goorden (Tourism & Management Studies)
Promoting products via Instagram is a rapidly growing phenomenon in the world of online advertising. These advertisements’ ability to stand out and obtain desired consumer outcomes has become increasingly challenging due to the enormous amount of advertisements already present on this platform. One strategy that can be useful is celebrity endorsement, which has – because of celebrities’ credibility and attractive characteristics – proven to be an effective way to create favourable attitudes and stronger purchase intentions. The present study investigated the effects of an Instagram advertisement with an (in)genuine, smiling celebrity on consumers’ behaviour. More specifically, this study examined differences between consumers from two countries: the Netherlands and Spain. An online experiment with two conditions was conducted (i.e. ingenuine vs genuine, smiling celebrity). The sample included 174 Dutch and 137 Spanish participants. The results reveal that the type of smile significantly affects consumers’ purchase intentions. Attitudes towards the celebrity also influence the effect of the type of smile on purchase intention. National background was thus found to play a moderating role.